Incident subjective memory complaints and the risk of subsequent dementia. (9th September 2014) - Luck, T.; Luppa, M.; Matschinger, H.; Jessen, F.; Angermeyer, M. C.; Riedel‐Heller, S. G.
<x xml:space="preserve">Abstract</x> Objective In this study, we aimed to analyze the association between new—incident—subjective memory complaints (SMC) and risk of subsequent dementia in a general population sample aged 75+ years. Method Data were derived from follow‐up (FUP) waves I‐V of the population‐based Leipzig Longitudinal Study of the Aged (LEILA75+). We used the Kaplan–Meier survival method to estimate dementia‐free survival times of individuals with and without incident SMC and multivariable Cox proportional hazards regression to assess the association between incident SMC and risk of subsequent dementia, controlled for covariates. Results Of 443 non‐demented individuals, 58 (13.1%) developed dementia during a subsequent 5.4‐year follow‐up period. Participants with incident SMC showed a significantly higher progression to dementia (18.5% vs. 10.0%; P = 0.010) and a significantly shorter mean dementia‐free survival time than those without (6.2 vs. 6.8 years; P = 0.008). The association between incident SMC and risk of subsequent dementia remained significant in the multivariable Cox analysis (adjusted hazard ratio = 1.8; P = 0.028). Conclusion Our findings suggest higher progression to dementia and shorter dementia‐free survival in older individuals with incident SMC. These findings support the notion that such subjective complaints should be taken seriously in clinical practice as possible early indicators of incipient dementia.